2004
DOI: 10.1074/jbc.m310836200
|View full text |Cite
|
Sign up to set email alerts
|

Regulated Shedding of PAR1 N-terminal Exodomain from Endothelial Cells

Abstract: G protein-coupled receptors can trigger metalloproteinase-dependent shedding of proteins from the cell surface. We now report that G protein-coupled receptors can themselves undergo regulated metalloproteinasedependent shedding. The N-terminal exodomain of protease-activated receptor-1 (PAR1), a G protein-coupled receptor for thrombin, displayed regulated shedding in endothelial cells, which normally express this receptor. Cleavage occurred at a site predicted to render the receptor unresponsive to thrombin. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 37 publications
2
43
0
Order By: Relevance
“…Consistent with the findings obtained for the h␤ 1 AR, the endothelin B, V 2 vasopressin, and thyrotropin receptors are cleaved in an activationdependent manner following agonist binding (36 -38, 42), although conflicting reports have been published for the thyrotropin receptor (44). On the other hand, the thrombin-mediated cleavage of PAR-1 has been shown to take place following protein kinase C activation (40), and furthermore, it has been shown that matrix metalloproteinase I can mediate the cleavage and activation of PAR-1, which leads to invasion and metastasis of tumor cells (41). Otherwise, the functional consequences of metalloproteinase-mediated cleavage have not been fully revealed for any other family A GPCRs.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Consistent with the findings obtained for the h␤ 1 AR, the endothelin B, V 2 vasopressin, and thyrotropin receptors are cleaved in an activationdependent manner following agonist binding (36 -38, 42), although conflicting reports have been published for the thyrotropin receptor (44). On the other hand, the thrombin-mediated cleavage of PAR-1 has been shown to take place following protein kinase C activation (40), and furthermore, it has been shown that matrix metalloproteinase I can mediate the cleavage and activation of PAR-1, which leads to invasion and metastasis of tumor cells (41). Otherwise, the functional consequences of metalloproteinase-mediated cleavage have not been fully revealed for any other family A GPCRs.…”
Section: Discussionsupporting
confidence: 73%
“…for endothelin B (35,36) and thyrotropin (37)(38)(39) receptors, and for the protease-activated receptor-1 (PAR-1) (40,41), which is the main GPCR for thrombin. The V 2 vasopressin receptor, on the other hand, has been shown to be cleaved at the interface between the second transmembrane domain and the first extracellular loop (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Several other proteases are also capable of cleaving and activating PAR2, as well as other PARs, but whether these proteases function as physiological regulators in vivo awaits validation. In addition, some proteases, including certain MMPs, disable PARs by cleaving downstream of the activation site, resulting in loss of the tethered ligand domain (Ludeman et al, 2004), and thus revealing a potentially important mechanism for regulation of PAR signalling in various cell types.…”
Section: Par Activationmentioning
confidence: 99%
“…The cleavage of this GPCR leads to the formation of a two-subunit receptor structure that is held together by disulphide bonds, the reduction of which can lead to the shedding of the receptor ectodomain (Couet et al, 1996). In addition to TSHR, the angiotensin II type 1 receptor and the protease-activated receptor-1 are the only other class A GPCRs, for which ectodomain shedding has been demonstrated (Ludeman et al, 2004;Cook et al, 2007).…”
Section: Introductionmentioning
confidence: 99%